Regeneration and Acclimatization of Salt-Tolerant Arachis hypogaea Plants Through Tissue Culture (Biological Sciences - PJSIR, 2006)
. Excised embryos of Arachis hypogaea were cultured on Murashige and Skoog’s medium (MS medium) supple- mented with different combinations of growth hormones. The highest frequency of callus proliferation (80%) was recorded on MS medium mixed with 1.0 mg/l of 2,4-D and 0.5 mg/l of BAP. These cultures were treated with 0.65 mg/l of trans-4- hydroxy-L-proline (HyP) and various concentrations (0.1-0.5%) of NaCl. In all cases the presence of salt reduced the fresh mass of callus. Shoot regeneration in the cultures took place when transferred to MS medium supplemented with 1.0 mg/l of kinetin (Kin) and 0.5 mg/l of 6-benzylaminopurine (BAP). Percentage of shoot regeneration decreased with the increase of NaCl (0.1- 0.5%) in the shoot regeneration medium. Root formation in these cultures took place when the cultures were nurtured on MS medium free of growth hormones. Regeneration, hardening and acclimatization of the salt- tolerant plants was conducted.